Does the surgical technique and the academic level of the hospital have impact on survival in gastric cancer? a retrospective study - Orman, Süleyman; Yalman, Haydar; Yiğitbaşı, Mehmet Rafet (International Surgery Journal, 2018)
Background: Cure may only be achieved through surgical resection in gastric cancer. In this paper, we retrospectively analyzed the effects of D1 and D2 dissection and type of the performed operation as well as type of the hospital on survival. Methods: Total of 125 patients, who had been operated for gastric cancer in two separate hospitals between January 2003 and June 2007 were retrospectively studied. The patients who met the criteria of the study were divided into four groups according to the operation type. Difference between the survival rates, median survival of the patients with respect to the type of the operation and hospitals were analyzed. Results: Of the patients, 66 had total gastrectomy + D1 lymph node dissection, 39 had distal subtotal gastrectomy + D1 lymph node dissection, 7 had total gastrectomy + D2 lymph node dissection, and 13 had distal subtotal gastrectomy + D2 lymph node dissection. Analysis of 3-year survival of the patients demonstrated no statistically significant difference between the groups with respect to the survival rates, median survival of the patients and the hospitals (p<0.05). Conclusions: This study indicated that there was no significant difference between survivals with regard to the institution where the operation had been performed, the operation type and the extent of the dissection.